Urban and rural infant-feeding practices and health in early medieval Central Europe (9th-10th Century, Czech Republic) - Kaupová, Sylva; Herrscher, Estelle; Velemínský, Petr; Cabut, Sandrine; Poláček, Lumír; Brůžek, Jaroslav (American journal of physical anthropology, 2014)
In the Central European context, the 9th and 10th centuries are well known for rapid cultural and societal changes concerning the development of the economic and political structures of states as well as the adoption of Christianity. A bioarchaeological study based on a subadult skeletal series was conducted to tackle the impact of these changes on infant and young child feeding practices and, consequently, their health in both urban and rural populations. Data on growth and frequency of nonspecific stress indicators of a subadult group aged 0-6 years were analyzed. A subsample of 41 individuals was selected for nitrogen and carbon isotope analyses, applying an intra-individual sampling strategy (bone vs. tooth). The isotopic results attest to a mosaic of food behaviors. In the urban sample, some children may have been weaned during their second year of life, while some others may have still been consuming breast milk substantially up to 4-5 years of age. By contrast, data from the rural sample show more homogeneity, with a gradual cessation of breastfeeding starting after the age of 2 years. Several factors are suggested which may have been responsible for applied weaning strategies. There is no evidence that observed weaning strategies affected the level of biological stress which the urban subadult population had to face compared with the rural subadult population.
Keywords: kojení; Carbon Isotopes; Infant; Humans; městské obyvatelstvo; kojenec; dítě; stable isotopes; History, Medieval; Child; Nitrogen Isotopes; Female; mladý dospělý; dospělí; Bone and Bones; odstavení; kosti a kostní tkáň; antropologie fyzická; lidé; Middle Ages; Weaning; předškolní dítě; Adult; venkovské obyvatelstvo; Great Moravian Empire; ženské pohlaví; Age Determination by Teeth; Anthropology, Physical; Czech Republic; izotopy dusíku; Young Adult; Rural Population; izotopy uhlíku; Tooth; breastfeeding; zuby; Česká republika; Breast Feeding; Child, Preschool; morbidity; určení zubního věku; Urban Population; dějiny středověku